1994
DOI: 10.1096/fasebj.8.1.8299894
|View full text |Cite
|
Sign up to set email alerts
|

Glucose‐dependent regulation of the l ‐pyruvate kinase gene in a hepatoma cell line is independent of insulin and cyclic AMP

Abstract: Hepatocyte-like mhAT3F cells have been derived from the hepatoma of a transgenic mouse expressing the SV40 large T antigen under the control of the antithrombin III gene regulatory region (Antoine, B., Levrat, F., Vallet, V., Berbar, T., Cartier, N., Dubois, N., Briand, P., and Kahn, A. (1992) Gene expression in hepatocyte-like lines established by targeted carcinogenesis in transgenic mice. Exp. Cell. Res. 200, 175-185; F. Levrat et al., unpublished results). In these cells, the L-PK gene is transcriptionally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
66
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 25 publications
4
66
0
Order By: Relevance
“…An activating region located around -3 kb is required for full promoter activity [79,88]. This region corresponds to a liver-specific DNAase I-hypersensitive site (HSS-2) [85] [93]. Since Foufelle et al [94] demonstrated that glucose must be converted into glucose 6-phosphate by a hexokinase to exert its action on gene transcription, Axel Kahn's group proposed that insulin is required for the production of glucokinase in hepatocytes while hepatoma cells may constitutively express hexokinases, thus bypassing the need for insulin [95].…”
Section: Tissue-specific Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…An activating region located around -3 kb is required for full promoter activity [79,88]. This region corresponds to a liver-specific DNAase I-hypersensitive site (HSS-2) [85] [93]. Since Foufelle et al [94] demonstrated that glucose must be converted into glucose 6-phosphate by a hexokinase to exert its action on gene transcription, Axel Kahn's group proposed that insulin is required for the production of glucokinase in hepatocytes while hepatoma cells may constitutively express hexokinases, thus bypassing the need for insulin [95].…”
Section: Tissue-specific Controlmentioning
confidence: 99%
“…While cycloheximide may block the insulin induction of glucokinase, it also inhibits a step downwards in the pathway of glucose stimulation of transcription. Indeed, Lefranqois-Martinez et al [93] showed that in their hepatoma cells the insulin-independent glucose stimulation of L promoter activity could still be blocked by cycloheximide. Insulin and glucose also stabilize the mRNA [96].…”
Section: Tissue-specific Controlmentioning
confidence: 99%
“…In these three glucose-sensitive tissues, glucose transport and phosphorylation are performed by various isoforms of glucose transporters and hexokinases, respectively. Glucose phosphorylation to glucose 6-phosphate, required for glucose action on the transcriptional machinery (2)(3)(4)(5)(6), is mainly mediated by hexokinase (HK) 1 II in adipocytes and by hexokinase IV (or glucokinase) in the liver and ␤ cells; expression of the glucokinase gene is constitutive in the pancreas and insulin-dependent in the liver due to the existence of two different tissue-specific alternative promoters (7). However, glucokinase is replaced by other insulin-independent hexokinase isoforms (mainly HK I) in cultured hepatoma cell lines (2,8,9).…”
mentioning
confidence: 99%
“…Glucose phosphorylation to glucose 6-phosphate, required for glucose action on the transcriptional machinery (2)(3)(4)(5)(6), is mainly mediated by hexokinase (HK) 1 II in adipocytes and by hexokinase IV (or glucokinase) in the liver and ␤ cells; expression of the glucokinase gene is constitutive in the pancreas and insulin-dependent in the liver due to the existence of two different tissue-specific alternative promoters (7). However, glucokinase is replaced by other insulin-independent hexokinase isoforms (mainly HK I) in cultured hepatoma cell lines (2,8,9). Tissues whose function is regulated by glucose also possess particular glucose transporters, GLUT 4 in adipocytes and GLUT 2 in tissues secreting glucose into the blood (liver, small intestine, and proximal tubular cells of the kidney) as well as GLUT 2 in the ␤ cells of the islets of Langerhans (10,11).…”
mentioning
confidence: 99%
See 1 more Smart Citation